Immature stages of two Neotropical species of Dasyhelea Kieffer, 1911 (Diptera: Ceratopogonidae) - Ronderos, Maria Marcela (2003)
Larva and pupa of Dasyhelea bahamensis (Johnson 1908) and Dasyhelea necrophila Spinelli and Rodríguez 1999, are described and illustrated by using a phase contrast stereoscope and scanning electron microscope. Dasyhelea bahamensis was collected from flooded, muddy areas in cohauila, Yucatan, Mexico, while D. necrophila were discovered in small artificial or plant-holding containers in Argentina and Mexico. Larvae of both species have character states typical of herbivorous ceratopogonid larvae.